Mechanism and Activity of Ni-Based (Ni-M: M = Fe, Mo, W, Ta) Cermet Anodes for Ammonia Oxidation in SOFCs. (2nd June 2015) - Hashinokuchi, Michihiro; Yokochi, Ryuji; Akimoto, Wataru; Doi, Takayuki; Inaba, Minoru; Kugai, Junichiro
Abstract : We investigated the activity for Ni-based (Ni-M: M = Mo, W and Ta) anodes for ammonia oxidation in SOFCs. It was found that Mo was the most effective additive for the anode cermets in this study. It was found that the activity for ammonia oxidation at Ni-Mo anode was determined by a balance between ammonia adsorption and nitrogen desorption, and synergetic effects of Ni and Mo improved the anode activity for NH3 oxidation.